A Novel Image Steganography (NIS) Technique (International Journal of Engineering and Computer Science, 2017)
With the growth in the communication, there is an increase in the transmission of data across the various medium; security is the key issue that needs to be addressed. Various steganography techniques are used to hide actual message secretly to provide control over the medium where data is sent. This paper is intended to propose an image steganography technique that will hide four bits of data in first component (blue) of a pixel in 24 bit RGB image. Security is employed in the secret key as secret key will decide the location where data is to be stored in the digital image and its length will depend upon the message length.